Risk factors for stunting in toddlers from a family perspective: A qualitative study in at-risk urban areas - Uun Kunaepah; Priyo Sulistiyono; Rahmani Azzahra; Eva Dwi Alviani (AcTion: Aceh Nutrition Journal, 2026)
Childhood stunting remains a major public health problem, and previous quantitative studies have not adequately captured family level experiences and risk dynamics. This study aimed to explore the risk factors for stunting in children under five years of age from the family perspective using an exploratory qualitative approach in the working area of Argasunya Primary Health Center in August 2025. Nine families with stunted children aged 0–59 months were purposively selected based on low socioeconomic status, low birth weight, and limited access to health services. Data were collected through in-depth interviews and home observations, validated by triangulation, and analyzed using inductive thematic analysis. The analysis generated key themes: mothers had adequate knowledge about stunting but did not fully translate it into optimal feeding and breastfeeding practices; families depended on unstable informal income; nutrition decisions were influenced by other family members; and children experienced recurrent infections in poor sanitation settings. The central conceptual finding, “know but can’t afford,” reflected the gap between what families knew and what they could do. The study concluded that vulnerability to stunting resulted from the interaction of internal and external family factors and highlighted the need for integrated, family centered prevention through social protection, improved sanitation and hygiene, and contextual family nutrition counseling